Study of incidence and outcome of acute inversion of uterus - Bangal, Vidyadhar B.; Gagare, Swati D.; Bhardwaj, Samita; Raut, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Acute inversion of uterus also called as puerperal inversion of uterus is a rare, but life-threatening complication of third stage of labour. Severe uterine atony, mismanagement of third stage of labour, adherent placenta are some of the common factors associated with the occurrence of acute inversion of uterus. Early recognition and prompt treatment are important to save life of the woman. Methods: A retrospective cross-sectional record-based study was carried out to find out the incidence, presentation and outcome of cases of acute inversion of uterus admitted to Pravara Rural Hospital Loni for a period of three years (October 2015 to September 2018). Results: During the study period, there were 27,134 deliveries including 8,834 caesarean sections. There were six cases of acute inversion of uterus in the hospital during study period. The incidence of acute inversion of uterus was 0.22 per one thousand deliveries (0.27 per thousand vaginal deliveries and 0.11per one thousand caesarean sections). Three cases were referred from outside hospital and three cases had delivered at Pravara Rural Hospital. Five cases had delivered vaginally, where as one case had undergone caesarean section. There were two maternal deaths and four survivals among six cases of inversion of uterus. Severe anaemia, irreversible hypovolemic shock and multi-organ failure were causes of maternal deaths. Conclusions: Prompt recognition of uterine inversion and its immediate reposition under anaesthesia was a key for successful management. Delay in recognition and transfer of cases resulted in haemorrhagic and neurogenic shock, leading to death of a women. Institutional deliveries with practice of principles of active management of third stage of labour (AMTSL) and improvement in emergency obstetric care services at peripheral hospitals, avoiding delays at all levels will help to reduce the incidence, morbidity and mortality associated with acute inversion of uterus.